Partial saturation in compacted soils : Geotechnique Symposium in Print 2011 - Gallipoli, Domenico (ICE Publishing, 2013)
'Partial Saturation in Compacted Soils' provides a comprehensive overview of recent advances in unsaturated soil mechanics, ranging from material testing to modelling and analysis of engineering boundary value problems, providing further insight into the rapidly developing topic of unsaturated soil mechanics and its application to compacted fills and serving as an invaluable reference for engineers and researchers for years to come.